Financial Performance Of PT Bank Rakyat Indonesia Before And After The Covid 19 Pandemic - Devita Yuliana; Priyo Utomo (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This study aims to determine, assess, and analyze the financial performance of PT Bank Rakyat Indonesia PERSERO Tbk as measured using the CAR, ROA, LDR, and BOPO ratios using financial statements from 2019 to 2021. The data collection technique used is secondary data observation. The data analysis technique used is qualitative descriptive analysis. And the data validity technique used is source triangulation. The theoretical implications in this study are seen from the calculation of CAR, ROA, and LDR: bank management needs to pay attention to the balance of high returns with the level of risk faced. Meanwhile, when viewed from the calculation of the BOPO ratio, banks need monetary policy and credit stimulus to continue to grow, maintain fiscal sustainability in the short and long term so that the costs incurred for operations are more effective and efficient, and prevent and handle COVID-19 from human aspects, especially health aspects. Practical implications of the results of this study can be used as a consideration for future researchers to expand the range of research by adding samples and using a longer observation period so that the results obtained are more concrete and volatile.